Development of a Diesel Engine Maintenance Textbook for Nautical Technology Students at West Sumatra Shipping Polytechnic - Syamsyir, Syamsyir; Uddin, Soleh; Erlinda, Nelfi; Basrizal, Basrizal (Civiliza Publishing, Indonesia., 2025)
This research focuses on the development of a structured and practice-based textbook for ship diesel engine maintenance aimed at Nautical Technology students at West Sumatra Shipping Polytechnic.The background highlights the increasing demand for skilled maritime workforce in Indonesia, contrasted with the lack of adequate teaching materials that combine theory and practice.The study aims to bridge this gap through a project-based learning approach. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation).Data were collected from students of the Nautical Technology study program and validated by two subject matter experts. Findings indicate that students had not been using proper printed resources and relied mostly on internet materials and lecturers explanations.The developed textbook received positive validation from experts with a score categorized as feasible with revision. Students' responses showed the textbook was attractive and effective in improving understanding and practical readiness.The research contributes to enhancing vocational education quality, strengthening the connection between theory and practice, and preparing competent graduates in maritime technology.It is concluded that the developed textbook is suitable for implementation with minor improvements, and further research is suggested to extend its application to other fields of maritime studies